Neutrophil and neutrophil-lymphocyte ratios as predictors of clinical characteristics in patients with Lymphangioleiomyomatosis - Yang, Lulu; Huang, Liting; Luo, Yingquan; Ren, Siying (Frontiers in Medicine, 2025)
ObjectivesLymphangioleiomyoma (LAM) is a rare multisystemic disease with variable clinical manifestations. This study aim to evaluate the potential of neutrophils and neutrophil-to-lymphocyte ratio (NLR) in predicting treatment response and prognosis in LAM.MethodsLymphangioleiomyoma patients hospitalized in the respiratory department from January 2013 to January 2024 were retrospectively collected. Baseline data, routine blood tests, pulmonary function, and lung computed tomography (CT) were recorded, and the NLR was calculated. Patients were divided into pneumothorax and no-pneumothorax groups based on pneumothorax occurrence. Differences between the two groups were compared, and significantly different indicators were further analyzed.ResultsA total of 78 patients with LAM were included in the study, 42 of them developed pneumothorax from registration to the end of follow-up, and 36 did not develop pneumothorax. There were differences in neutrophils, eosinophils, and NLR between the two groups (P < 0.05). Further analysis revealed that neutrophils and NLR were negatively correlated with lung function in LAM patients (P < 0.05), and positively correlated with lung CT grading and pneumothorax occurrence. Sirolimus treatment reduced neutrophil and NLR values in the pneumothorax group of LAM patients in (P < 0.05).ConclusionLymphangioleiomyoma patients with higher neutrophil and NLR values have worse lung function and may be more susceptible to spontaneous pneumothorax, and sirolimus treatment reduces neutrophil and NLR values in LAM patients with pneumothorax.